Perlindungan Terhadap Anak Penyandang Disabilitas Pasca Putusan Perceraian Orang Tua di Kabupaten Kolaka - Ramlia, Ramlia; Ratnawati, Ratnawati; Marwah, Marwah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This study aims to analyse the form of protection for children with disabilities after parental divorce and the role of the government in providing protection for children with disabilities after parental divorce. This research is empirical juridical in nature with data collection techniques derived from library research and field research. The results of this study indicate that: (1) the form of protection of children with disabilities after divorce decisions in Kolaka Regency is based on the rights of children with disabilities contained in Law Number 1 of 1974 concerning Marriage and Law Number 8 of 2016 concerning Persons with Disabilities, but has not been implemented optimally in accordance with the legislation; (2) The role of the Kolaka Regency government has not been optimal in carrying out its mandate based on Kolaka Regency Regional Regulation Number 3 of 2016 concerning the Implementation of Child Protection.